(untitled) (Konferensiyalar | Conferences, 2024)
This research article explores the challenges faced in intercultural communication within the context of multicultural education. With the increasing diversity of student populations in educational settings, effective communication between individuals from different cultural backgrounds is critical for fostering inclusive and equitable learning environments. This article examines the key challenges that educators encounter in intercultural communication and provides insights into strategies for addressing these challenges. By understanding the barriers to effective intercultural communication, educators can enhance their ability to promote cross-cultural understanding and create a supportive learning environment for all students.